Pengelompokan Hasil Evaluasi Pembelajaran Metode Hafalan Al Qur’an Tawazun Menggunakan Metode K-Means - Ajeng Khalili Rahmatiningsih; Agung Nilogiri; Ari Eko Wardoyo (Publikasi Indonesia, 2022)
The method of memorizing the Qur'an Tawazun is a method that maximizes the use of the right brain and left brain, allowing a person to memorize, understand, and believe. Each category has several assessment points as a benchmark for the ability of students, which are used to overcome the level of failure of students in each category of learning the method of memorizing the Qur'an tawazun. The results of the evaluation of the learning of the tahfidz Islamic boarding school Daarul Huffadz Indonesia in 2020 were felt to be less than optimal, because the learning process was carried out simultaneously. This can be seen from the difference in scores that are quite different in each category of assessment. Based on the previous problem, it is necessary to group the results of the evaluation of learning the Qur'an memorization method. The goal is that every student gets maximum treatment and provides convenience for the institution, as well as teaching staff to carry out learning. The purpose of this study is to determine the optimum number of clusters as well as members of each cluster by measuring cluster performance using the Davies Bouldin Index (DBI) method and implementing the K-Means algorithm. The K-Means algorithm is a non-hierarchical data clustering method that is able to group large amounts of data, relatively quickly, and efficiently. This study uses 401 observational data and 12 attributes. From the calculation results, the optimal number of clusters lies in 2 clusters, with a Davies-Bouldin Index (DBI) value of 1.439. There are 26 members of cluster 1, and 375 members of cluster 2.